Ketaksaan Leksikal dalam Lagu “Glow Like Dat” dan “See Me” Karya Rich Brian - Frans Sayogie; Angga Ilham Perdana; Munawar Aidil; Shania Andre (Buletin Al-Turas, 2019)
Tulisan ini membahas tentang ketaksaan leksikal dalam lagu “Glow Like Dat” dan “See Me” karya Rich Brian. Ketaksaan leksikal dalam lagu  dapat menyebabkan penyampaian pesan mengalami kendala pemaknaan budaya, bahasa, sosiologis, dan psikologis. Tujuan dari penelitian ini adalah untuk mengidentifikasi bentuk leksikal yang digunakan di dalam lagu  tersebut apakah mengandung ketaksaan leksikal, dan kemudian menganalisis bentuk ketaksaan leksikal  dan makna kata-kata  dalam lirik lagu. Metode penelitian yang digunakan adalah  metode deksriptif kualitatif  dan metode non-participant observation sebagai teknik pengumpulan data. Data yang dianalisis diambil dari lirik lagu “Glow Like Dat” dan “See Me” karya Rich Brian yang kemudian diklasifikasikan ke dalam beberapa kategori ketaksaan leksikal dan pemaknaannya.  Temuan penelitian yang diperoleh adalah ketaksaan leksikal yang terdapat di dalam lagu  “Glow Like Dat” dan “See Me” karya Rich Brian dapat diklasifikasikan sebagai homonimi berbentuk homofon, serta polisemi yang dikemas dalam bentuk kata slang. Kesimpulan penelitian ini adalah pemahaman terhadap pemaknaan leksikal dalam lagu berbahasa Inggris  sangat penting  bagi penutur bukan berbahasa Inggris agar memperoleh pemahaman makna lagu yang komprehensif. This paper discusses lexical ambiguities in the songs "Glow Like Dat" and "See Me" by Rich Brian. Lexical ambiguities of the songs can cause the delivery of messages to experience constraints of meanings in cultural, language, sociological, and psychological aspects. The purpose of this study is to identify the lexical forms used in the songs whether they contain lexical ambiguities, and then to analyse the lexical ambiguities forms and meaning of words in song lyrics. The research method used is a qualitative descriptive method and a non-participant observation method as data collection techniques. The data analysed were taken from the lyrics of the songs "Glow Like Dat" and "See Me" by Rich Brian, which were then classified into several categories of lexical ambiguities and their meaning. The research findings obtained are the lexical ambiguities contained in the songs "Glow Like Dat" and "See Me" by Rich Brian can be classified as homonymy in the form of homophones and polysemy which are packaged in slang words.  The conclusion of this study is that the understanding of lexical meanings in English songs is very important for non-English speakers to gain a comprehensive understanding of the meaning of the songs.